Dutch Disease Economics A case Study of Indonesia - Rini Yayuk Priyati (Universitas Islam Indonesia, 2009)
The term ‘Dutch disease’ was first used to describe the indirect effects of the boom in the gas sectorin the Netherlands in the 1960s on other sectors. This paper applies this framework to analysethe impact of the 2007-2008 surge in oil and gas prices in Indonesia. It finds that this has induced areal appreciation of the Rupiah. In contrast to ‘Dutch disease’ theory, it has been accompanied bygrowth in agricultural and manufacturing exports. The simulation results suggest that the observedreal appreciation due to the booming energy has inhibited the growth of Indonesian exports of agriculturaland manufacturing products.Keywords: Dutch disease, energy, agricultural and manufacturing exports